Conceptual repair of indirect in• guinal hernia. - Croci, Fabio; Pérez Penco, Ernesto (Cirugía del Uruguay, 1987)
The conceptual surgery of indirect inguinal hernia re• quires an exhaustiva anatomical and functional study of the deep inguinal ring, whose containment failures explain the mecanisms of hernia appearance. The delicate valvular mechanism of the deep inguinal ring is the most important anti-herniary factor. When it fails, the habitation of the congenital peritoneal diverticulum takes place. A technical system of fascio-ligamentary repair of indirec inguinal hernia has been developed based on this concept. This method has been used for three years in more than a hundred patients, with very good results.